Application of Monitoring and Evaluation for Land in Africa (MELA) Framework in 12 African Countries - CGIAR Research Program on Policies, Institutions, and Markets (2017)
PIM researchers worked with African Land Policy Centre to develop a Monitoring and Evaluation framework for assessing progress on land governance in Africa. The MELA framework is being piloted by 12 countries in Africa. This allows tracking of progress on commitments made under the AU Declaration on Land Governance in Africa, including commitments to land rights for women and special groups, e.g. pastoralists.